2020
DOI: 10.1021/acscatal.0c02909
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Nature of Active Sites for Methanol Synthesis from CO/CO2 on Cu/CeO2

Abstract: CO2 hydrogenation to methanol can play an important role in meeting the sustainability goals of the chemical industry. In this study, we investigated in detail the role of the Cu–CeO2 interactions for methanol synthesis, emphasizing the role of the copper surface and interface sites between copper and ceria for the hydrogenation of CO2 and CO. A combined CO2–N2O titration approach was developed to quantify the exposed metallic copper sites and ceria oxygen vacancies in reduced Cu/CeO2 catalysts. Extensive char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 81 publications
(138 reference statements)
4
80
0
Order By: Relevance
“…The blocking of oxygen vacancies by in situ formed carbonates may explain their limited role in CO 2 hydrogenation. 21 , 45 , 75 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blocking of oxygen vacancies by in situ formed carbonates may explain their limited role in CO 2 hydrogenation. 21 , 45 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…We propose that the ceria-induced inhibition of the rWGS is associated with the higher formate coverage, which blocks metallic Cu sites active in the rWGS as proposed before. 45 , 78 81 Besides the blocking of Cu surface by formate, in situ CO-to-CH 3 OH conversion during CO 2 hydrogenation can also contribute to the ceria-induced inhibition of the rWGS. It has been reported that Cu–CeO 2 interface is highly active for CO hydrogenation to CH 3 OH.…”
Section: Resultsmentioning
confidence: 99%
“…2. In the formate (HCOO*) mechanism, 259,302,303 Regarding the Cu/ZnO system, many hypotheses on the nature of the active sites were proposed. 259,304,305 Fujita et al 306 investigated the system with diffuse reflectance FT-IR spectroscopy and temperature-programmed desorption, showing that two types of formate species and zinc methoxide -Zn(CH 3 O) 2form during the reaction.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…. In the formate (HCOO*) mechanism,259,302,303 CO* 2 is hydrogenated to HCOO*, H 2 COO* (or HCOOH*), and to H 2 COOH*. Then, an OH* is removed, yielding H 2 CO*, which is hydrogenated to H 3 CO* and CH 3 OH.…”
mentioning
confidence: 99%
“…The calculated adsorption energies of Cu n on CeO 2 (110), absolute values of 2.971-3.492 eV, are generally higher than the abovementioned values for other surfaces, suggesting strong interactions between copper and ceria. In addition, experimental studies reported that nanostructured Cu/CeO 2 catalysts had a copper particle size-activity dependence 51 , which thus strongly stimulates further study of larger Cu cluster adsorption on CeO 2 (110).…”
Section: Discussionmentioning
confidence: 96%